2001
DOI: 10.1105/tpc.13.1.125
|View full text |Cite
|
Sign up to set email alerts
|

sas1, an Arabidopsis Mutant Overaccumulating Sodium in the Shoot, Shows Deficiency in the Control of the Root Radial Transport of Sodium

Abstract: A recessive mutation of Arabidopsis designated sas1 (for sodium overaccumulation in shoot) that was mapped to the bottom of chromosome III resulted in a two-to sevenfold overaccumulation of Na ؉ in shoots compared with wild-type plants. sas1 is a pleiotropic mutation that also caused severe growth reduction. The impact of NaCl stress on growth was similar for sas1 and wild-type plants; however, with regard to survival, sas1 plants displayed increased sensitivity to NaCl and LiCl treatments compared with wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 45 publications
0
25
1
Order By: Relevance
“…Plants that are mutated in the sas1 gene, which causes overaccumulation of sodium in the shoots, exhibit a severely repressed growth phenotype (Nublat et al, 2001). However, although the AtRabG3e transgenic plants showed increased sodium content in the shoots (Fig.…”
Section: The Effects Of Atrab7 (Atrabg3e) On Salt Localizationmentioning
confidence: 99%
“…Plants that are mutated in the sas1 gene, which causes overaccumulation of sodium in the shoots, exhibit a severely repressed growth phenotype (Nublat et al, 2001). However, although the AtRabG3e transgenic plants showed increased sodium content in the shoots (Fig.…”
Section: The Effects Of Atrab7 (Atrabg3e) On Salt Localizationmentioning
confidence: 99%
“…To examine more directly the role of SOS1 in controlling Na ϩ transport from the root to the shoot, we measured the Na ϩ content in the xylem sap from sos1 mutant and wild-type plants. The method of xylem sap collection was as described by Gaymard et al (1998) and Nublat et al (2001). The Na ϩ concentration in the xylem sap of both sos1 mutant and wild-type plants increased substantially over time in 100 mM NaCl, but the Na ϩ content was always higher for sos1 (Figure 8).…”
Section: Role Of Sos1 In Controlling Long-distance Na ؉ Transportmentioning
confidence: 99%
“…In preliminary experiments (data not presented), we found that plants whose roots were treated with 10 mM TEA 1 and 3 mM Cs 1 wilted, an effect not seen with other inhibitors that we used. So, in the experiments that we report involving TEA 1 and Cs 1 treatments, we reduced transpiration by keeping the plants in a chamber with 100% relative humidity (compare with Nublat et al, 2001;Shi et al, 2002). In these experiments, we added the inhibitors at the same time as the salt; S. maritima is a saltaccumulating plant and has a strong capacity for Na 1 accumulation, so it adjusts very rapidly to increase in external Na 1 concentration (Clipson, 1987).…”
Section: Teamentioning
confidence: 99%
“…Each treatment, which lasted between 48 and 144 h (see figure and table legends or the text for details) under the conditions described above, had eight replicates with three plants per beaker. Where TEA-Cl, CsCl, or BaCl 2 was included in the treatment, the relative humidity of the growth chamber (Sanyo MLR-350HT growth cabinet; Sanyo Electrical and Biomedical; photosynthetically active radiation of 200 mmol m 22 s 21 ) was maintained at 100% to minimize the effect of transpiration on Na 1 accumulation (compare with Nublat et al, 2001;Shi et al, 2002), since these three inhibitors caused plants to wilt. For treatments with BaCl 2 , MgCl 2 (0.5 mM) replaced MgSO 4 (0.5 mM) in the Hoagland nutrient solution.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%